The antagonist and synergist potential of cholinium-based deep eutectic solvents - Macário, Inês P. E. (2021)
The design of environmentally friendlier solvents has gained increasing relevance in the last decade. Deep eutectic solvents (DES) have recently emerged, with advantages like low-cost and putative lower environmental impact. However, information about DES toxicity is still scarce. This work aims to contribute to profiling the ecotoxicity of DES based on cholinium chloride ([Chol]Cl). Six DES were addressed, combining [Chol]Cl (as hydrogen bond acceptor - HBA) with ethylene glycol, glycerol, 1,2-propanediol, propionic acid, 1-propanol, and urea as hydrogen bond donors (HBD), in different molar ratios. The Microtox® Acute Toxicity Test, was used for assessing their toxicity towards the marine bacteria Allivibrio fischeri . Because the dissociation of DES in water is expected, analysis appraising the mixtures toxicity theory should be considered, which is a step forward in this field. This analysis suggested that [Chol]Cl and all HBD with the exception of propionic acid:[Chol]Cl 1:2 and 4:1 behave antagonistically, which is contrary to what has been suggested previously. The most extreme cases are Urea:[Chol]Cl and 1-Propanol:[Chol]Cl, with EC50 values higher than their starting materials dosed singly, configuring very promising and biocompatible alternative solvents. Toxicity was found to be dependent on DES composition, as well as on molar proportions of the starting materials.